فنية السرد في القصة الجزائرية القصيرة موسم الوجع لعبد الرشيد هميسي أنموذجا - تواتي ابراهيم, حمزة; عقاب, المعتز; قديري, فاروق (University of Eloued جامعة الوادي, 2024)
هدفت الدراسة إلى استنتاج الخصائص والسمات السردية في المجموعة القصصية "موسم الوجع" للأديب عبد الرشيد هميسي، وذلك من حيث تحليل كل ما له علاقة بالفنية والرمزية من سيمائية العنوان والغلاف إلى فنية توظيف كل من؛ الشخصيات، المكان، الزمان، القيم، التناص. ومن خلال منهجي الوصف والتحليل، توصلت الدراسة إلى أن المجموعة القصصية تميزت بتصوير فني وإبداعي من خلال السمات الفنية للسرد.This study aimed to deduce the narrative characteristics and features in the short story collection "Season of Pain", written by Abd El-Rachid Hameesi. This was achieved by analyzing all aspects related to artistic and symbolic elements, from the semiotics of the title and cover to the artistic use of characters, setting, time, values, and inter-textuality. We used both descriptive and analytical methods. We found that the short story collection is distinguished by artistic and creative depiction through the narrative's artistic features.
أدب حديث ومعاصر
Keywords: السرد، الفنية، القصة، المجموعة القصصية، "موسم الوجع".; Narrative; Artistic; Story; Short Story Collection; Season of Pain